Polymorphism in Conservative Structures? The Scapulocoracoids in Skates Genus Psammobatis (Chondrichthyes, Arhynchobatidae) and the Validity of P. parvacauda - Mabragaña, Ezequiel (2020)
Skeletal structures, especially the claspers, neurocrania, and scapulocoracoids have been widely used to characterize and describe new species of elasmobranchs. Intra and interspecific variation of scapulocoracoids in 3 species of Psammobatis (n = 94) from the Southwest Atlantic Ocean were analyzed to assess its utility as a diagnostic character in skates. Moreover, based on scapulocoracoids and body morphometric analyses, the validity of Psammobatis parvacauda McEachran, 1983 was evaluated. A remarkable sexual dimorphism in scapulocoracoids was observed in all species in accordance with original descriptions, which was also evident in the principal component (PCA) and Discriminant Analyses. The number and arrangement of post-dorsal and post-ventral fenestra were highly variable at intra-specific level, in contrast with original descriptions. Particularly, one of the morphotypes observed in females of P. normani was identical to the one reported in P. parvacauda. Results showed intraspecific variation in this structure, as was previously observed in Sympterygia species. Therefore, this structure should not be used as a diagnostic character in skates, at least for these genera. Regarding body morphometry the PCA showed that P. parvacauda grouped with P. normani females and the cross-validated analysis showed that P. parvacauda was classified in the group of P. normani females. P. parvacauda is only known from its original description (one female) and a likely second specimen, but our analyses revealed a lack of diagnostic characteristics. Based on observations and measurements of the holotype of P. parvacauda, and comparisons with congenerics, P. normani is regarded a senior synonym of P. parvacauda.